Arizona Twin Project: Specificity in Risk and Resilience for Developmental Psychopathology and Health. (23rd December 2019) - Lemery-Chalfant, Kathryn; Oro, Veronica; Rea-Sandin, Gianna; Miadich, Samantha; Lecarie, Emma; Clifford, Sierra; Doane, Leah D.; Davis, Mary C.
Abstract: The Arizona Twin Project is an ongoing longitudinal study designed to elucidate gene–environment interplay underlying the development of risk and resilience to common mental and physical health problems during infancy, childhood and adolescence. Specificity of risk is carefully examined across mental and physical health and how these influences vary across socioeconomic and sociocultural environments. Participants are a sample of approximately 700 twins (31% Latinx) recruited from birth records in the state of Arizona, USA. Twins are 32% monozygotic twins, 36% same-sex dizygotic (DZ), 32% opposite-sex DZ, currently 10–11 years of age. Primary caregivers were interviewed on twins' development and early physical and social environments when twins were 1, 2 and 5 years of age. In-depth objective measurement commenced in middle childhood, with in-person assessments at 8–11 years of age, with plans to continue to follow the sample across adolescence. Middle childhood measures focus on children's physical and mental health, including diurnal cortisol, actigraphy-based measures of sleep and activity, cold pressor task assessing acute pain, and reaction time tasks assessing executive functioning. Preliminary findings illustrate that objective assessments of children's health are highly heritable, but they do not always share genetic etiology with more commonly used subjective assessments. Exposure to early adversity moderates genetic influences on both executive functioning and health, with higher heritability typically seen under adverse conditions. Future directions include an examination of how pubertal stage affects genetic and environmental influences on diurnal cortisol, sleep, chronic pain, and mental health.